Assessment and Comparison of the Mechanical Properties of Laser Welded Joints in Docol 1200M and Strenx S700MC Steel Alloy Grades Under Impact Loads - Paweł PROCHENKA; Jacek JANISZEWSKI (Problemy Mechatroniki)
The article evaluates the strength and ductility of laser butt joints made of 2 mm Docol 1200 M martensitic steel sheets based on the hardness, quasi-static and dynamic tensile tests. Technological research of laser welding process was carried out on welding cell using IPG fiber – based welding source with 6 kW maximum power. The tests were carried out for parallel and perpendicular orientation of specimens by rolling direction. In addition, the obtained results were compared with the analogous results obtained during the Strenx S700 MC steel tests. Dynamic tests were performed using the tensile split Hopkinson pressure bar technique with strain rates of 103 s-1. The obtained results showed that the strength of Docol 1200 M under dynamic tensile test conditions are similar to the material strength under static tensile test conditions. However, due to the breaking of the specimens in the heat affected zone, the strength of the welded joint is much lower than in base material, which was not observed during the Strenx S700 MC steel tests.